VD_FINDINFO Décision / 2018 / 892 vom 11. Oktober 2018 - VD Tribunal cantonal (2018)
REJET DE LA DEMANDE, RÉCUSATION, DÉCISION D'IRRECEVABILITÉ | 310 CPP (CH), 393 al. 1 let. a CPP (CH), 56 let. f CPP (CH), 59 CPP (CH)